2020
DOI: 10.18006/2020.8(5).676.682
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF THE ANTIOXIDANT AND Α-AMYLASE INHIBITORY ACTIVITIES OF Mitragyna inermis (WILLD) O. KUNTZE AND Tamarindus indica LINN.

Abstract: The current study was conducted to explore the antioxidant and anti-diabetic potential of Tamarindus (T.) indica and Mitragyna(M.) inermis aqueous leaves extracts. Along with this, the estimation of available total phenolics and total flavonoids contents was also carried out to establish the scientific background of the antioxidant and anti-diabetic potential of used plants. For estimation of total phenolics and total flavonoids contents, Folin-ciocalteu and Aluminium chloride (AlCl3) colorimetric method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 91 publications
1
6
0
Order By: Relevance
“…The observed high antioxidant activity of some plant extracts may be attributed to high concentrations of phenolic compounds with potential protective effects (Spanou et al, 2010). Furthermore, these findings supported previous results on the antioxidant activity of S. hermonthica (Kiendrebeogo et al, 2005), C. grandis (Deshpande et al, 2011), C. quadrangularis (Prabhavathi et al, 2016;Tiwari et al, 2021), D. hirtiflora (Adeniran et al, 2020;Sonibare & Abegunde, 2012), G. alata (Zheleva-Dimitrova et al, 2017 and M. inermis (Ouédraogo et al, 2020) using different extraction solvents.…”
Section: An Oxidant Ac Vitysupporting
confidence: 87%
“…The observed high antioxidant activity of some plant extracts may be attributed to high concentrations of phenolic compounds with potential protective effects (Spanou et al, 2010). Furthermore, these findings supported previous results on the antioxidant activity of S. hermonthica (Kiendrebeogo et al, 2005), C. grandis (Deshpande et al, 2011), C. quadrangularis (Prabhavathi et al, 2016;Tiwari et al, 2021), D. hirtiflora (Adeniran et al, 2020;Sonibare & Abegunde, 2012), G. alata (Zheleva-Dimitrova et al, 2017 and M. inermis (Ouédraogo et al, 2020) using different extraction solvents.…”
Section: An Oxidant Ac Vitysupporting
confidence: 87%
“…The results of the study by Razali et al ( 29 ) showed that the methanolic extract obtained from maceration expressed antioxidant capacity close to that of the standard compound rutin (1.65 vs. 1.72 mmol TE/g dried weight), as ethyl acetate and hexane extracts possessed lower capacities (0.7 and 0.5 mmol TE/g dried weight, respectively). The ABTS •+ radical scavenging capacity determined in Ouédraogo et al's ( 47 ) study using aqueous extract was 7067.6 μmol AAE/g extract, which can be calculated as half of the positive control, quercetin (14550.2 μmol AAE/g).…”
Section: Resultsmentioning
confidence: 95%
“…Eight studies conducted by Krishnaveni et al resulted in 2.3–8.3 mg AAE/g extract ( 30 , 31 , 35 – 37 , 39 – 41 ). Ouédraogo et al ( 47 ) reported a value of 667.26 μmol AAE/g extract, which was ~10% of standard quercetin (6034.6 μmol AAE/g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Phyllanthus (P.) amarus Schum & Thonn. and Striga (S.) hermonthica are plants used in traditional medicine throughout the world, particularly by the herbalists of Bobo-Dioulasso in the management of diabetes 10,11,12 . This study has been initiated in order to investigate the free DPPH radicals scavenging and α-amylase inhibitory activities of these plants.…”
Section: Introductionmentioning
confidence: 99%